Implementation of autonomous decision protocols for emergency medical dispatchers: caller satisfaction survey and evolution of practices - Clarence Fischer; Gaëlle le Bail; Anna Ozguler; Jérémie Boutet; Charles Groizard; Michel Baer; Thomas Loeb (International Journal of Emergency Medicine)
Abstract Background Access to emergency care is becoming increasingly challenging due to rising demand and limited resources, such as shortage of general practitioners (GP). In France, emergency medical services (EMS) have experienced a 23% increase in call volume over the past decade. To address this, French dispatch systems are evolving, with Emergency Medical Dispatchers (EMDs) empowered to make certain medical decisions through Autonomous Decision Protocols (ADP). These ADP were designed for most frequent and simple emergency situations such as low back pain, epistaxis, head and limb injury, anxiety, and allowed EMDs to recommend medical advice, send an ambulance or refer the caller to a dispatching doctor. Aim This study aimed to assess callers’ satisfaction with decisions made by EMDs using ADPs compared to decisions made by medical doctors with similar chief complaint. Material & method The study was prospective, involving all ADP calls from September to October 2023. All calls concerning ADPs and dispatched by EMDs were included. Callers were called back within a few days of the call in order to obtain their experience using a questionnaire. Retrospective patient files concerning similar chief complaints handled in the traditional way, over the same period in the previous year, were used for comparison. Results A total of 358 calls were analyzed, with 217 (61%) callers completing a satisfaction survey. The results showed high satisfaction, with an average score of 8.6/10. The most common chief complaints were head and limb injuries, and the vast majority (90%) of callers felt their expectations were met. Only a small percentage (4%) required a second opinion or follow up due to worsening symptoms. Conclusion The findings suggest that ADPs improved efficiency by providing standardized medical advice, reducing unnecessary ambulance dispatches, and saving medical resources. Callers who benefited from ADPs were generally satisfied with the service, with satisfaction rates comparable to those found in international studies. Expanding ADPs to cover additional medical conditions could further enhance emergency dispatch systems, especially in light of increasing demand and reduced medical resources.